Calculations of seismic loads of the Rezaksai Reservoir (Международный научный журнал «Инженер», 2026)
The paper considers the design load on different cross-sections and vibrations of water pipes, obtained empirically and confirmed by theoretical formulas. When constructing the epuray of the calculated equal force, all loads are summarized. The time incompatibility of local design loads is not taken into account. Finding the equal force of loads and their distribution throughout the volume of the structure, taking into account the simultaneity of action in all sections is carried out according to the formula A. L. Mozhevitinov and V. N. Bukhartsev.